Determinan Capaian Standar Pelayanan Minimal (SPM) pada Pelayanan Kesehatan Orang Beresiko Terkena HIV dengan Pendekatan Malcolm Baldrige di Puskesmas Kota Depok Tahun 2022 - Rora Asyulia; Sutanto Priyo Hastono (Syntax Literate, 2023)
Quantitative research with a cross-sectional design (Cross Sectional) will examine the achievements of health service programs for people at risk of getting HIV using the Malcolm Baldrige approach at the Depok City Health Center. The purpose of this study was to determine the performance of the health service program for people at risk of getting HIV using the Malcolm Baldrige approach. The population of this study were all Community Health Centers in Depok City, totaling 38 Health Centers. The research instrument used questionnaires and interviews which were made based on standard references from Malcolm Baldrige's criteria which had been translated into Indonesian by previous researchers and adapted to the research objectives. There are 6 independent variables, namely leadership, strategic planning, focus on customers, measurement analysis and knowledge management, focus on workforce and process management, while the dependent variable is the achievement of MSS in health services for people at risk of getting HIV. Data analysis used univariate data analysis to look at the frequency distribution of performance outcomes, bivariate data analysis looked at the relationship between 6 (six) Malcolm Baldrige criteria and the performance outcomes of the Health Service Program for people at risk of getting HIV at the Depok City Health Center and multivariate analysis to find the most dominant influencing factor achievement of SPM HIV. The majority of research results fall into the category of unfavorable leadership (53.07%), strategic planning (46.21%) focus on customers (43.84%), measurement, analysis and knowledge management (44.21%), workforce (47 ,85%) and process management (47,49%) . Paldal multivalial analysis value R = 0.749 on valrialbel X (leadership valrial in customer focus) with Y valrial (SPM HIV skill) shows a high quality relationship in positive, whereas in return the leadership valrial in focus on customer malcal halsil performance in SPM Alkaline HIV is increasingly increasing . The value of the coefficient of determination (R squalre) shows a value of 0.561, which is obtained from the regression model obtained in terms of 56.1%, the valrial rating is dependent on the calculation of the SPM HIV with the Focus on the failure which has the greatest influence on the performance evaluation of the MSS HIV (48.5%).